PENGARUH LIKUIDITAS, PROFITABILITAS DAN PERTUMBUHAN PENJUALAN TERHADAP KEBIJAKAN DIVIDEN - Olivia Maria Luisiana Sumarno Dwi Saputra (JURNAL EKONOMI DAN KEWIRAUSAHAAN, 2015)
Companies that make the payment of dividends to its investors is a company that has a profit and good financial structure, if the company can increase the dividend payment, then this is evidence of the improvement in the performance of the company. The financial performance of the company can be analyzed through financial ratios, namely through the liquidity ratios, profitability and sales growth. The purpose of this study was to analyze the significance of the effect of liquidity, profitability and sales growth partially or simultaneously on dividend policy on manufacturing companies in Indonesia Stock Exchange. Analyzing the dominant variable influence (liquidity, profitability and sales growth) on dividend policy on manufacturing companies in Indonesia Stock Exchange. In conclusion, that there was a significant effect of independent variables, namely liquidity, profitability and sales growth partially or simultaneously to the dependent variable is the dividend policy (Y) in a manufacturing company in Indonesia Stock Exchange. The results of the analysis we concluded that the profitability variable dominant influence on dividend policy (Y) in a manufacturing company in Indonesia Stock Exchange. Keywords: liquidity, profitability, sales growth, dividend policy